1983
DOI: 10.1007/bf00436886
|View full text |Cite
|
Sign up to set email alerts
|

Saprophytic fungi isolated from the hair of domestic and laboratory animals with suspected dermatophytosis

Abstract: Hair samples from domestic and laboratory animals with suspected dermatophytosis were examined for the presence of saprophytic fungi. A nutritionally poor base medium, developed by the author, was used in the isolation and identification of the saprophytes. Three hundred and ninety-four specimens were examined of which 246 were from dogs, 75 from cats, 30 from horses, 19 from cows, 12 from guinea pigs, 5 from rats, 2 from parakeets, 2 from chinchillas and one each from a goat, a mink and a lesser panda (Ailuru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
0
25
1
3
Order By: Relevance
“…The other fungal isolate was Alternaria spp by air borne fungi or by fungi in soil; some of them in 15 samples (0.12%). All patients were treated either have potential allergenic activity [21]. with oral griseofulvin or ketoconazole or itraconazole.…”
Section: Resultsmentioning
confidence: 99%
“…The other fungal isolate was Alternaria spp by air borne fungi or by fungi in soil; some of them in 15 samples (0.12%). All patients were treated either have potential allergenic activity [21]. with oral griseofulvin or ketoconazole or itraconazole.…”
Section: Resultsmentioning
confidence: 99%
“…Otcenasek and Dvorak (1962) reported that T. terrestre was probably only a skin contaminant of small mammals from South Eastern Moravia. Aho (1983) isolated T. terrestre from different animals including goats. The other identified species namely T. rubrum (1.7% of total isolates) was isolated in rare frequency from sheep hairs and was not encountered from different substrates as reported by several researchers from all over the world (Abdel-Hafez et al, 1991; El-Said, 1996, 2002; El-Said and Abdel-Hafez, 1995; Ali-Shtayeh et al, 1988a, b, 2000; Alghalibi, 2001; Moses and Sunday, 2001; Shukia et al, 2003; Periasamy et al, 2004; Dobrowolska et al, 2006; Ulfig, 2006; Thanaa et al, 2008 and others).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of keratinophilic fungi on hairs of various animals has been briefly reviewed by numerous researchers in many parts of the world (Rees, 1967; Gugnani et al, 1975; Aho, 1980, 1983; Lopez-Martinez et al, 1984; Bagy and Abdel-Hafez, 1985; Bagy, 1986; Ali-Shtayeh et al, 1988a, b, 2000; Kubo et al, 1990; El-Said and Abdel-Hafez, 1995; El-Said, 1996, 2002; Rashid et al, 1996; Camin et al, 1998; Gugnani, 2000; Hubalek, 2000; Alghalibi, 2001; Moses and Sunday, 2001; Shukia et al, 2003; Periasamy et al, 2004; Dobrowolska et al, 2006; Ulfig, 2007; Thanaa et al, 2008 and others).…”
mentioning
confidence: 99%
“…Bu durum; özeııikle kötü ahır hijyenine (karanlık, nemli, havasız, sıkışık) bağlı olarak, hayvanların kıl örtüsü üzerinde latent bulunan çok sayıda mantar sporlarının hızla üremesi ve bunun, besi yerlerinde gelişmesi oldukça zor olan trichophytie türlerinin üre-mesini engellemesinden kaynaklanmış olabilir. Aynı bulgular diğer araştırıcılar (2,15,18,29) tarafından da doğrulanmaktadır.…”
Section: Tartışma Ve Sonuçunclassified